A Self-Determination Theory and Acceptance and Commitment Therapy-based intervention aimed at increasing adherence to physical activity - Lev Arey, Dalit; Blatt, Asaf; Gutman, Tomer (Frontiers in Psychology, 2022)
The purpose of the present study was to evaluate the effectiveness of physical activity (PA) intervention program designed to enhance levels of engagement in PA. Despite robust evidence supporting the beneficial effects of PA on overall health, only about 22% of individuals engage in the recommended minimum amount of PA (Piercy & Troiano, 2018). Recent surveys suggested that most individuals express intentions to be physically active (EU, 2017), though the psychological state of amotivation dismissed these struggles (Caudwell & Keatley, 2016). In the current study, we pilot-tested a new intervention program, aimed at enhancing engagement in PA among sedentary individuals. The intervention was based on two behavioral change and motivational psychological frameworks: Self-Determination Theory (SDT; Deci & Ryan, 1985) and Acceptance and Commitment Therapy (ACT; Hayes et al., 1999). During a 14-week intervention program, 94 sedentary Israeli college students (Mage=24.4, SD=1.42, Females = 89) were randomly assigned into one of three groups: SDT and ACT-based intervention, traditional intervention, and a non-treatment group. Prior to and following the intervention, participants completed the Behavioral Regulation in Exercise Questionnaire-3 (BREQ-3) to examine motivation to exercise and the International Physical Activity Measurement) IPAQ) to evaluate their training frequency. Results showed that the SDT and ACT-based intervention group exhibited a significant increase in motivation to exercise between time 1 and time 2, while the other two groups (i.e., the traditional intervention program and the non-treatment group) showed insignificant differences in motivation to exercise. Furthermore, neither of the groups showed significant differences in their training frequency per week. However, those in the SDT and ACT-based group reported an increase in activity intensity from time 1 to time 2 compared to the two other groups. Further, exercise psychology consultants and scholars can use the intervention protocol and utilize these findings to improve PA behaviors and promote health in the general population. Limitations, future directions, and implications are discussed in detail.